Citra Indonesia pada Golongan Priayi Jawa melalui Corak Pendidikan Barat - Gian Fajar Gemilang (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The specialty of the priayi group is based on high status in the social strata of indigenous peoples. Priayi group has access to the wider Western world than other indigenous peoples although it still has restrictions with Europe. Some planned to be like the predecessors who worked in the colonial government and others chose to elevate the status of their people just like the Europeans. Through Western education, they are hoping can advance indigenous peoples and create a new social identity. With the technique of literature studies and using historical methods, this study aims to find out the contribution of the priayi group to the existence of the Indonesian state through Western education during Dutch colonialism. Studies show the education they get becomes the solution to the social problems of the Dutch East Indies community. Social equality has inspired them to enculturate as a step of harmonization of indigenous peoples and form a nationalist spirit as the one Indonesian people. The struggles of the priayi group become a picture of supporting the success of Indonesian society that gives the fruit of the thought to live a community life today.